Attitude of Government School Teachers of Pokhara Metropolitan City Towards Teaching Profession - Poudel, Upendra Prasad (Far Western Journal of Education, 2025)
The performance of the students highly depends upon the attitude of the teacher’s t towards their profession. This study aims to find out the attitude of the government school teachers of Pokhara valley towards teaching profession which directly affects i the learning of the students and overall teaching learning process. To assess the attitude of teachers, thirty teachers from ten schools were selected as the respondents with random sampling. Likert type attitude scale was constructed with 50 statements. Content validity of the scale was established by the judgement of four experts of the subject area and 27 percent upper and lower group method was used to determine the power of discrimination of the statements. Finally, 32 statements were accepted. A z square norm and interpretation criteria were developed. Under the quantitative research design, the attitude scale questionnaire survey is used to find the attitude. The research came in to the conclusion that only one fifth of the teachers are have favorable attitude towards their teaching profession and major percentage of teaching faculties have neutral and unfavorable attitude towards the profession. The concerned stakeholder should timely address the dissatisfaction of the teachers towards their profession and should focus on morale, motivation and issues of order of precedence which shall bring a new energy to the teachers.